Nutritional strategies to increase efficiency of masculinization, growth performance and feed utilization of the African catfish Clarias gariepinus - Adenigba, Issa Ayankunle (University of the Philippines Visayas, 2018)
This study was conducted to evaluate growth, survival, sex-ratio, nutrient utilization of testosterone propionate sex-reversed Clarias gariepinus fed with optimized oyster meal as fishmeal replacement. The first study conducted was on feeding trials to evaluate the effects of dietary pine pollen from Pins tabulaeformis Carr. On masculinization, growth, food coversion efficiency, and survival of Clarias gariepinus. Experimental diets were prepared using a commercial feed for fry, as basal diet with 5 levels of pine pollen supplementation : 0 (control, T1), 80 (T2), 160 (T3), 320 (T4), and 640 (T5) mg kg-1 diet, two positive control diets s feeding trials were conducted, the first ; larvae to fry for 72 days (Phase 1) and the second ; fry to fingerling for an additional 45 days (Phase 2). Results showed that the percentage of males was significant lower in the untreated diet (50.4%) and significantly higher in all of the pine groups although there was no significant difference between the pine pollen groups. The male percentage was significantly highest in the 17-a-methyltestosterone and testosterone groups with no significant difference between the two groups. Pine pollen resulted in slightly but significantly inferior androgenic effect, but anabolic effect was superior compared to either 17-a-methyltestosterone, and testosterone. Its use for sex reversal and improved growth is recommended. In the second study, an 8-week feeding trial was conducted to evaluate different levels of oyster meal (Crassostrea irridalei) as replacement of fishmeal in formulated diets for normal African catfish (NAC) Clarias gariepinus. Five experimental diets containing various inclusion levels of oyster meal which replaced fish meal were formulated. Diet 1 contained 0% oyster meal, while Diets 2-5 contained 25%, 50%, 75%, 100%, oyster meal, respectively. The third study investigated the effects of starvation and subsequent reffeding on growth, feed utilization, body composition, haematological indices, morphological and plasma biochemical parameters for sex-reversed African catfish Clarias gariepinus fingerlings. The fish were subjected to 4 feeding regimes : continuous feeding control group : (C- T1); 2 days starvation followed by 8 days refeeding (T2: 2:8), 4 days starvation followed by 16 days refeeding (T3 :4:16) and 8 days starvation followed by 32 days refeeding (T4:8:32), respectively. The results indicated that sex-reversed African catfish subjected to 2, 4,8 days of food deprivation and refeeding exhibited compensation for WG with a coefficient of 1.21, 1.17, and 1.15 for T2, T3, T4, respectively.